ANALISIS TATANIAGA CABAI MERAH (CAPSICUM ANNUM L) DI KECAMATAN RANAH PESISIR, KABUPATEN PESISIR SELATAN - Rini Hakimi; Fania Handayani; Rika Hariance (Journal of Integrated Agribusiness, 2023)
An efficient agricultural commodity trade system can increase the income of farmers. This study aims to describe the channels and functions of the trading system by each institution as well as to analyze the trading system margin, the share received by farmers, and the efficiency of the red chili marketing channel in Ranah Pesisir District, Pesisir Selatan Regency. The method used is a qualitative and quantitative descriptive method where the data collection uses a survey method. The results showed that the red chili marketing channel pattern uses intermediary traders. That are collectors and retailers. The marketing function performed by farmers and red chili collectors/retailers consists of exchange, physical, and facility functions. The trading system margin on channel one is smaller compared to channel two. The percentage share of the price farmers receive in channel one is higher than in channel two. Channel one is more efficient than channel two. Trading administration institutions must pay attention to the physical function (transportation, storage, and packaging) of distributing red chilies to maintain their quality of red chilies.